Stigmasterol Modulates Allergic Airway Inflammation in Guinea Pig Model of Ovalbumin-Induced Asthma - Aaron Opoku Antwi; David Darko Obiri; Newman Osafo (Mediators of Inflammation)
We explored the potential benefits of stigmasterol in the treatment of asthma, an airway disorder characterized by immune pathophysiology and with an ever-increasing worldwide prevalence. We assessed the modulatory effect of the intraperitoneal administration of stigmasterol on experimentally induced airway inflammation in guinea pigs. The effect of stigmasterol on inflammatory cell proliferation, oxidative stress, lung histopathology, and remodeling was investigated. The results showed significant suppressive effects on ovalbumin-induced airway inflammatory damage. Stigmasterol at 10–100 mg/kg reduced proliferation of eosinophils, lymphocytes, and monocytes while reducing peribronchiolar, perivascular, and alveolar infiltration of inflammatory cells. Histopathology revealed stigmasterol maintained lung architecture and reversed collagen deposition, an index of lung remodeling. Overexpression of serum vascular cell adhesion molecule-1 (VCAM-1) and ovalbumin-specific immunoglobulin E (OVA sIgE) elicited by ovalbumin sensitization and challenge was significantly controlled with stigmasterol. Taken together, stigmasterol possessed significant antiasthmatic properties and had suppressive effects on key features of allergen-induced asthma.